Ammonia-based chemisorption heat pumps for cold-climate heating applications: A comprehensive review. (October 2020) - Yang, Zhiyao; Qu, Ming; Gluesenkamp, Kyle R.
Highlights: New Clapeyron diagram compares 66 chemisorption working pairs. Innovative developments are reviewed for materials, components, and system designs. Research priorities are matching salts to applications and reducing thermal mass. Hysteresis and reaction heat of sorbent salts significantly affect performance. Abstract: This article reviews the state of the art of chemisorption heat pumps that use ammonia as the refrigerant for cold-climate heating applications. In such a system, ammonia vapor is adsorbed by the solid salt through reversible chemisorption reactions, and the thermal effect of the reaction and ammonia phase change is used to extract heat from a cold environment and supply heat to a warm environment. With the high latent heat and low boiling point of ammonia as a low-temperature refrigerant and the high sorption capacity of ammonia-based chemisorption reactions, chemisorption heat pumps have the potential to produce high-efficiency heating, particularly for cold climates. This review first briefly introduces the basics of ammonia-based chemisorption heat pump systems. Then, the latest development of sorbent materials, including ammoniate salts and heat-conductive porous matrix materials, are summarized with the focus on low-temperature heating conditions. The design of system components, as well as cycle configurations, in the literature are summarized. This review concludes with highlights of recent developments on these topics and suggestions of areas for further research.